Analysis of the NCR Mechanisms in Hanseniaspora vineae and Saccharomyces cerevisiae During Winemaking - Lleixà, Jessica; Martín, Valentina; Giorello, Facundo; Portillo, Maria C.; Carrau, Francisco; Beltran, Gemma; Mas, Albert (Frontiers in Genetics, 2019)
There is increasing interest in the use of non-Saccharomyces yeasts in winemaking due to their positive attributes. The non-Saccharomyces yeast Hanseniaspora vineae is an apiculate yeast that has been associated with the production of wine with good fermentation capacity and an increase in aromatic properties. However, this yeast represents a concern in mixed culture fermentation because of its nutrient consumption, especially nitrogen, as its mechanisms of regulation and consumption are still unknown. In this study, we analyzed the nitrogen consumption, as well as the nitrogen catabolism repression (NCR) mechanism, in two genome-sequenced H. vineae strains, using synthetic must fermentations. The use of synthetic must with an established nitrogen content allowed us to study the NCR mechanism in H. vineae, following the amino acid and ammonia consumption, and the expression of genes known to be regulated by the NCR mechanism in S. cerevisiae, AGP1, GAP1, MEP2 and PUT2. H. vineae exhibited a similar amino acid consumption and gene expression profile to S. cerevisiae. However, the wine strain of S. cerevisiae QA23 consumed ammonia and valine more quickly and, in contrast, tyrosine and tryptophan more slowly, than the H. vineae strains. Our results showed a similar behavior of nitrogen regulation in H. vineae and S. cerevisiae, indicating the presence of the NCR mechanism in this Hanseniaspora yeast differentiated before the whole genome duplication event of the Saccharomyces complex. Future study will elucidate if the NCR mechanism is the only strategy used by H. vineae to optimize nitrogen consumption.